Fire-Resistant Building Materials And Their Safety Standards - Ghaniya Alijon; Jakhongir Khazratkulov (Zien Journals, 2025)
This article examines in detail the types of fire-resistant building materials, their physical and chemical properties, their behavior at high temperatures, as well as international and national fire safety standards. The role of concrete, brick, mineral and basalt wool, fire-retardant coatings, intumescent paints, and flame retardants in ensuring the fire resistance of buildings is analyzed. Particular attention is paid to the use of fire-resistant materials in Uzbekistan and their development prospects
Keywords: fire-resistant materials; fire safety; basalt wool; mineral insulation